Innovative Mobile and Internet Services in Ubiquitous Computing Proceedings of the 11th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2017) - Barolli, Leonard; Enokido, Tomoya (Advances in Intelligent Systems and Computing,, 2018)
This book highlights the latest research advances, new methods and development techniques, challenges and solutions from both theoretical and practical perspectives related to Ubiquitous and Pervasive Computing (UPC), with an emphasis on innovative, mobile and internet services. With the proliferation of wireless technologies and electronic devices, there is a rapidly growing interest in UPC, which makes it possible to create human-oriented computing environments in which computer chips are embedded in everyday objects and interact with the physical world. With UPC, people can go online even while moving around, thus enjoying nearly permanent access to their preferred services. Though it holds the potential to revolutionize our lives, UPC also poses a number of new research challenges. The book gathers the proceedings of the 11th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2017), held on June 28-June 30, 2017in Torino, Italy.